Yang Kotor yang Menyucikan: Sakralitas Darah Menstruasi Perempuan dalam Jejaring Kultural (Pela) di Maluku - Oita, Stevanus; Lattu, Izak Y.M; Nuban Timo, Ebenhaizer I (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
This article aims to describe and explain the culture of pela blood or cultural networking in the people of Lumahpelu and the Sohuwe Country indigenous community on Seram Island, Maluku. Interviews, documentary studies and literature studies are used to obtain data. During this time the stigma that appears in society about menstrual blood is something that is dirty and unclean, thus separating individuals from the community. But this article reveals that menstrual blood integrates the people of the home country and the country of Sohuwe as a pela bond. Pela bonds live through the sacrality of menstrual blood which is the implementation of the ceremonies of the period of cultural transition (pinamou). This article concludes that blood circulation is a collective identity that contains the value of solidarity.